A ANALISIS PENGARUH PRICE EARNING RATIO (PER), CURRENT RATIO (CR) DAN TOTAL ASSETS TURNOVER (TAT) TERHADAP RETURN SAHAM (STUDI KASUS PADA SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2021 - Sari, Lusi Pramita; Kardinal, Kardinal (Publikasi Riset Mahasiswa Manajemen, 2023)
Abstract : This study aims to determine the effect of Price Earning Ratio , Current Ratio and Total Asset Turnover On Stocks Return (Study On Agricultural Sector Listed On The Idx In 2017-2021. Sampling technique with purposive sampling technique. The sample used was 19 companies from 26 manufacturing companies listed on the Indonesia Stock Exchange (IDX), so that the data analyzed amounted to 95 which were then transformed into 89 data. The data analysis technique used is descriptive statistical analysis. Based on the results of this study indicate that Price earning ratio has a significant negative effect on stocks return, Current Ratio has a positive and no significant effect on stocks return, total asset turnover has a negative and no significant effect on stocks return. Price Earning Ratio , Current Ratio and Total Asset Turnover together influence stocks return.